KARAKTERISTIK IMAGING CT-SCAN PADA PENDERITA BATU GINJAL DAN BATU SALURAN KEMIH DI RSUP PROF NGOERAH TAHUN 2021-2022 - Pradana, I Gede Agus; Anandasari, Pande Putu Yuli; Margiani, Ni Nyoman; Suadiatmika, Dewa Gde Mahiswara (Essence of Scientific Medical Journal; Vol 21 No 2 (2024): Volume 21 No. 2 (Juli - Desember 2023) Essential: Essence of Scientific Medical Journal, 2024)
ABSTRACT Introduction: Kidney stones or as known as nephrolithiasis is a condition where stones form in the renal pelvis. Stones that enter the urine collection system including the ureters, urinary bladder and urethra are called urolithiasis. The gold standard for diagnosing kidney stones and ureteral stones is CT-Scan with the stone type density assessment parameter used is Hounsfield units (HU). Method: This study used a retrospective descriptive cross-sectional design. Samples were selected based on inclusion and exclusion criteria. The research location was at Prof. Ngoerah Hospital for 6 months using total sampling techniques. Data processing uses SPSS ver. 25 with univariate analysis. Results: Secondary data from CT-Scan medical records on kidney and urinary tract stone sufferers at Prof Ngoerah General Hospital in 2021-2022 found 123 samples and 89 samples met the inclusion criteria Discussion: Based on the gender group, the most common gender was male in 55 patients (61.8%). Based on age group, most were found in the 51-60 year age group with 27 patients (30.3%). Based on the location of the stone, most were found in the lower calyces in 33 patients (37.1%). Based on the most common stone size, namely <5 mm, there were 24 patients (27.0%). Based on calyces dilation, the majority were not found in 51 patients (57.3%). Based on ureteral dilation, the majority was not found in 68 patients (76.4%). Conclusion: Dominant characteristics were found in male gender, age group 51-60 years, lower calyx location, HU density 200-450, stone size < 5 mm, no enlargement of calyces and ureters was found. Key words: Kidney stones, ureter stones, CT-Scan